Assessment of Discomfort Experienced by School Children While Performing 'ART' and 'MCP'-An Experimental Study. - R S Goud; L Nagesh; F Shoba; H G Raju (Frontiers in Dentistry, 2012)
Atraumatic Restorative Treatment (ART) is a minimal intervention technique in the management of carious lesions, which results in negligible discomfort to the patient. The aim of this study was to assess and compare the discomfort levels during Atraumatic Restorative Treatment and Minimal Cavity Preparation (MCP: a method using rotary instruments) treatment procedures in a sample of school children in Davangere city.An experimental study was performed aimed at comparing discomfort levels as measured by subjective (Venham index) and objective (Heart rate) methods at six specified moments during the treatment. A total of 200 children were randomly divided into two groups of 100 each. In each child, one class II restoration with GIC in a deciduous molar was performed. One group received treatment using rotary instruments (MCP) and the other group with ART. Discomfort levels were measured using Venham index (behavioural dimension) and heart rate (physiological dimension).The behavioural measurement revealed that in ART group the majority of the children(64%) showed an overall Venham score of '